Study of transient magnetic reconnection and its relation with the variability of the polar cap potential - Germán Fariñas Pérez (2015)
The polar cap potential is an important parameter available to describe the level of magnetospheric activity. It is a measure of the intensity of the magnetospheric convection. The convection process in the magnetosphere is not steady even under constant solar wind conditions. Bursty and unsteady processes in the magnetopause and in the magnetotail disturb the steady state of the magnetosphere and produce variability of the polar cap potential. In this work a three dimensional global magnetohydrodynamic simulation was analyzed in order to study transient magnetic reconnection at the dayside magnetopause and in the geomagnetic tai1. The Block-Adaptive- Tree-Solarwind-Roe-Upwind-Scheme (BATS-R-US) code was used. Transient reconnection events associated with flux transfer events at the dayside magnetopause and instabilities at the magnetotail neutral sheet current were identified. Finally the influence of these events on the variations of the polar cap potential has been analyzed.